2006
DOI: 10.1159/000093333
|View full text |Cite
|
Sign up to set email alerts
|

ZZ/ZW sex chromosome system in an undescribed species of the genus <i>Apareiodon </i>(Characiformes, Parodontidae)

Abstract: The chromosomes of an undescribed species of the genus Apareiodon (Characiformes, Parodontidae) from the Verde River, a headwater affluent of the Tibagi River (Paraná State, Brazil), were investigated using conventional Giemsa and Ag stainings, C-banding, CMA3 fluorescence and fluorescent in situ hybridization (FISH) using 18S and 5S rDNA probes. The diploid chromosome number was 2n = 54, with the karyotype composed of 48 meta/submetacentric and six subtelocentric chromosomes in males, and 47 meta/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 43 publications
(31 reference statements)
2
52
0
1
Order By: Relevance
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 58%
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 58%
“…Vicari et al (2006) chromosomically characterized Apareiodon sp. collected in the Verde River, a tributary of the Tibagi River (Paraná) belonging to the hydrographic system of the upper Paraná River.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle differences are present in the chromosome morphology (A. ibitiensis has 50 meta-submetacentric and 6 subtelocentric chromosomes) and the NORs are single in Apareiodon sp. and multiple in A. ibitiensis (Table 4) (MoreiraFilho et al, 1984(MoreiraFilho et al, , 1985Jesus & Moreira-Filho, 2000a;Vicari et al, 2006;Bellafronte et al, 2009). Also, in studies with satellite DNAs, Schemberguer et al (2011) considered Apareiodon sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some species apparently lack differentiated sex chromosomes, others bear a clear heteromorphic ZZ/ZW sex system. All these species appear to share the same sex chromosome differentiation by increasing heterochromatic segments and accumulation of repetitive DNAs in the W chromosome from an ancestral homomorphic pair [Centofante et al, 2002;Vicente et al, 2003;Rosa et al, 2006;Vicari et al, 2006]. A satellite DNA family composed of a 200-bp unit (pPh2004) was isolated from the genome of Parodon hilarii using genomic DNA restriction [Vicente et al, 2003].…”
Section: Accumulation Of Repetitive Dna Sequences In Fish Sex Chromosmentioning
confidence: 99%